PEDIATRIC HEALTHCARE SERVICE FOR AS A PART OF INDONESIAN FUTURE - Lothar Matheus Manson Vanende Silalahi (Faculty of Medicine Universitas Kristen Duta Wacana, 2021)
Continuing and accelerating child health are issues stated in Sustainable Development Goals (SDG) by United Nation (UN). Targets in improving child health in SDG are by decreasing neonatal and pediatric mortality. Reducing risk and prevention of neonatal mortality may be achieved by monitoring intrauterine fetal development. High burden of pediatric mortality may be seen in pediatric genetic, neoplasm and infectious disease. In this COVID-19 pandemic era, SARS-COV2 infection in children add more challenge in improving child health. In this issue, we proudly present articles on pediatric genetic, neoplasm and infectious disease especially in clinical manifestation, diagnostic and therapeutic challenge.